Perilaku Penggunaan Aplikasi Online Travel Agent (OTA) Oleh Konsumen Generasi Z Untuk Berwisata - Fahlevi, Renza; Steffani, Steffani; Sihombing, Dame Afrina (Universitas Islam Kadiri, 2024)
Developments in technology have contributed to the progress of the tourism industry, including in the online travel agent (OTA) business. OTA business competition in Indonesia is quite high, especially targeting Z generation (gen Z) consumers. This research aims to conduct a study of the intention of gen Z consumers in using OTA. This research consists of three independent variables, namely perceived ease of use, perceived usefulness and trust. The number of respondents in the research was 248 and the research data was collected using a questionnaire. The data was processed using linear regression techniques using the SPSS application. The results are explain that the three variables have an influence on the intention of gen z consumers to use OTA. The results of the study will contribute to OTA providers to understand the behavior of using OTA applications by gen Z consumers for traveling.